Blackwater: the rise of the world's most powerful mercenary army - Scahill, Jeremy (Nation Books, 2007)
The unauthorized story of the epic rise of one of the most powerful and secretive forces to emerge from the U.S. military-industrial complex, hailed by the Bush administration as a revolution in military affairs, but considered by others as a dire threat to American democracy